C-reactive protein-based screening of people with tuberculosis symptoms: a diagnostic accuracy study - Derendinger, Brigitta; Mochizuki, Tessa K.; Marcelo, Danaida; Shankar, Deepa; Mangeni, Wilson; Nguyen, Hanh; Yerlikaya, Seda; Worodria, William; Yu, Charles; Nguyen, Nhung Viet; Christopher, Devasahayam Jesudas; Theron, Grant; et al. (American journal of respiratory and critical care medicine, 2025)
Rationale: C-reactive protein (CRP)-based tuberculosis (TB) screening is recommended for people with HIV. However, its performance among people without HIV and in diverse settings is unknown. - - Objectives: In a multicountry study, we aimed to determine whether CRP meets the minimum accuracy targets (sensitivity ⩾ 90%, specificity ⩾ 70%) for an effective TB screening test. - - Methods: Consecutive outpatient adults with cough ⩾2 weeks from five TB endemic countries in Africa and Asia had baseline blood collected for point-of-care CRP testing and HIV and diabetes screening. Sputum samples were collected for Xpert MTB/RIF Ultra (Xpert) testing and culture. CRP sensitivity and specificity (5 mg/L cut-point) was determined in reference to sputum test results and compared by country, sex, and HIV and diabetes status. Variables affecting CRP performance were identified using a multivariate receiver operating curve regression model. - - Measurements and Main Results: Among 2,904 participants, of whom 613 (21%) had microbiologically confirmed TB, CRP sensitivity was 84% (95% confidence interval [CI], 81-87%) and specificity was 61% (95% CI, 59-63%). CRP accuracy varied geographically, with higher sensitivity in African countries (⩾91%) than Asian countries (64-82%). Sensitivity was higher among men than women (86% vs. 78%; difference, +8%; 95% CI, 1-15%) and specificity was lower among people with HIV than people without HIV (64% vs. 45%; difference, +19%; 95% CI, 13-25%). Receiver operating curve regression identified country and measures of TB disease severity as predictors of CRP performance. - - Conclusions: Overall, CRP did not achieve the minimum accuracy targets, and its performance varied by setting and in some subgroups, likely reflecting population differences in mycobacterial load.
Gesehen am 20.08.2025